Flottledsåterställning i norra Sverige - Styffe, Johan (2008)
In an effort to evaluate the effects of restorations of float ways on population density of stream dwelling fish in relation to the changes in habitat, I studied the physical habitat restored and channalized sites and their population density of brown trout (Salmo trutta L.) in three streams in the municipality of Sorsele. The differences between the channalized and the restored sites where most noticeable regarding substrate which where generally coarser in the restored sites. The analyses showed that the proportion of habitat that where suitable to the age class 0+ where significantly lower in the restored sites compared to the channalized sites. Regarding age class ≥2+, no statistical differences in habitat quality were found. For age class 1+ the proportion of good habitat was significantly higher in restored than in channalized sites. Only the age class 1+ showed a significantly higher population density in restored sites compared to the channalized sites. A possible reason to why there where no positive response for the other age classes might be the diversified need of habitat of the three age classes. It's also possible that the lack of positive response to restoration might be explained by a bottleneck situation in the streams, i.e. the habitat improvement for one age class is levelled out by a reduction of habitat quality for another age class.